Technoference in infant feeding: the impact of maternal digital media use during breastfeeding on maternal attention and mother-infant interactions - Mason, Emma M.; Riccabona, Tyne M.; Ventura, Alison K. (Frontiers in Developmental Psychology, 2024)
Introduction: Parents' sensitivity and responsiveness to their infants may be affected by the widespread availability and use of mobile devices. The present study examined the impact of maternal digital media use on maternal attention and the quality of mother-infant interaction during breastfeeding. Methods: Mothers and infants (n = 25 dyads) participated in a within-subject experiment. Mothers breastfed their infants under one experimental and one control condition, counterbalanced across two laboratory visits. During the Digital Media condition, mothers watched a television show on a tablet. During the Control condition, mothers listened to classical music at ambient levels. Video records were later coded to assess maternal attention to the infant, tablet, or elsewhere and evaluate the quality of mother-infant interaction. Results: There were more disruptions in maternal attention to the infant during the Digital Media (M = 3.7, S.E. = 0.2 per minute) versus Control condition (M = 1.7, S.E. = 0.2 per minute, p < 0.001). The proportion of the meal duration mothers spent focused on their infant was significantly lower during the Digital Media (M = 52.5%, S.E. = 3.9) versus Control condition (M = 83.9%, S.E. = 4.0%, p < 0.001). Lower maternal attention to the infant was associated with lower maternal sensitivity to cues (p = 0.03) and cognitive growth fostering (p = 0.002), as well as lower infant clarity of cues (p = 0.001). Lower maternal attention was also associated with less socioemotional growth fostering (p < 0.001) and lower infant responsiveness to the mother (p < 0.001) regardless of whether digital media was present or absent, but during the Digital Media condition, mothers engaged in more socioemotional growth fostering (p = 0.004) and infants were more responsive to mothers (p = 0.03). Discussion: The presence of digital media during infant feeding led to more interruptions to mothers' attention to their infants and time spent focused on digital media displaced time spent focused on the infant. The degree to which mothers were attentive to their infant versus digital media was a more important predictor of some aspects of interaction quality than the mere presence of digital media.